Type A aortic dissection: Are there CT signs suggestive of valvular involvement?. Issue 11 (November 2016) - Platon, Alexandra; Bernard, Stephane; Perrin, Nils; Murith, Nicolas; John, Gregor; Perneger, Thomas; Rutschmann, Olivier T.; Poletti, Pierre-Alexandre
Highlights: Non-ECG gated CT rarely shows valve involvement in type A aortic dissection. Diameters of the aortic root in type A aortic dissection were measured on initial CT. Sinus of Valsalva diameter >45 mm is 100% specific to predict aortic valve involvement. Abstract: Aim: To identify the predictive signs of aortic valve involvement on the non-electrocardiogram (ECG)-gated admission computed tomography (CT) of patients with Type A aortic dissection (AD) according to the Stanford classification. Materials and methods: We retrospectively analyzed the non-ECG-gated CT examinations of patients admitted to the emergency department who underwent surgery for Type A AD over a period of 4 years. The diameter of the following structures was calculated as the mean of the smallest and largest diameters (mm) measured in two different planes: aortic annulus, sinus of Valsalva, sinotubular junction, and proximal ascending aorta. These parameters were compared against operative reports in order to determine whether they were predictive of aortic valve involvement. Results: In total, 20 patients (13 men and 7 women) of a mean age of 59.5 years (29–80) were included, 55% of patients (11/20) having surgically proven valvular involvement. The mean diameters (in mm) of the aortic annulus, sinus of Valsalva, sinotubular junction and proximal ascending aorta in the group with (and without, respectively) valvular involvement was 27.7 (26.7), 44.3 (38.1), 42.6 (36.6), and 47.8 (45.9). Only the measurement of the mean diameter of the sinuses of Valsalva was significantly predictive (p = 0.02) of aortic valve involvement. Conclusion: Our findings suggest that measuring the diameter of the sinuses of Valsalva on non-ECG-gated admission CT examinations allows for predicting aortic valve involvement in Type A AD patients.